Usage of novel Co-MOF for mode-locked pulse generation near 2 μm - Ahmad, Harith; Chiam, J.W.; Samion, Muhamad Zharif; Ismail, Mohammad Faizal; Mutlu, Saliha; Filiz, Volkan; Sevil, Savaskan Yilmaz; Arsu, Nergis; Zaini, Muhammad Khairol Annuar; Thambiratnam, Kavintheran; Bayang, Leonard; Sun, Shufeng; et al. (Institute of Electrical and Electronics Engineers Inc., 2025)
In this work, we investigated unprecedented laser-induced rapid synthesis (LIRS) cobalt-based metal-organic framework (Co-MOF) saturable absorber (SA) to generate a conventional soliton pulse in a thulium-doped fiber laser (TDFL). The Co-MOF was drop-casted onto a side-polished fiber (SPF) to prepare the saturable absorber (SA). It exhibited a high modulation depth of 14 and a saturation intensity of 20.7MW/cm2. The pulse produced had a pulse width and center wavelength of 1.34 ps and 1974.2 nm, respectively. The repetition rate of the output was 13.09 MHz, which gives a pulse interval of about 76.4 ps. The beam output reached an average power of 6.56 mW and pulse energy of about 501 pJ before breaking, achieving a maximum peak power of 374 W. © 1965-2012 IEEE.